The Influence of Perception of Learning Media and Self-Confidence on English Speaking Ability - Anton, Muhammad; Suendarti, Mamik; Hasbullah, Hasbullah (Gema Wiralodra, 2025)
Speaking skills are the ability to speak fluently and proficiently in expressing thoughts or ideas. To develop this ability, a speaker must not only master vocabulary and phrases and have correct pronunciation, but also possess confidence in speaking. The purpose  of this study was to find out: 1). The effect of perceptions of learning media and self-confidence together on the English speaking ability of State Junior High School students in South Jakarta, 2). State in South Jakarta, 3).The influence of self-confidence on the ability to speak English for students of SMP Negeri in South Jakarta,. The sample used was 84 students as a sample with multiple linear regression analysis model. Based on the results of the hypothesis and data analysis, it is concluded as follows: 1). There is a significant influence on the perception of learning media and self-confidence together on the English speaking ability of State Junior High School students in South Jakarta. This is evidenced by the value of Sig = 0.000 <0.05 and Fcount = 19.239, 2). There is a significant influence on the perception of learning media on the English speaking ability of State Junior High School students in South Jakarta. This is evidenced by the value of Sig = 0.004 <0.05 and tcount = 2.989, 3). There is a significant effect of self-confidence on the English speaking ability of State Junior High School students in South Jakarta. This is evidenced by the value of Sig = 0.000 <0.05 and tcount = 4.347.